Magnesium supplementation enhances insulin sensitivity and decreases insulin resistance in diabetic rats - Liu, Hongzhou (Iran J Basic Med Sci, 2020)
OBJECTIVE(S): Diabetes mellitus has been suggested to be the most common metabolic disorder associated with magnesium deficiency. This study aimed to investigate the effects and mechanisms of magnesium supplementation on insulin receptor activity in elderly type 2 diabetes using a rat model and to provide experimental evidence for insulin resistance improvement by magnesium supplementation. MATERIALS AND METHODS: Rat model of type 2 diabetes was developed using a high-fat diet along with low dose streptozotocin (STZ) treatment. Magnesium supplement was given orally by mixing with the high-fat diet. Serum insulin level, insulin sensitivity, and insulin receptor affinity were assessed using radioimmunoassay (RIA). Insulin receptor, insulin receptor substrate (IRS-2), and β-Arrestin-2 gene and protein expression levels were measured using immunohistochemistry and RT-PCR. Xanthine oxidase assay, thiobarbituric acid reactive substance assay (TCA method), colorimetric assay, and ELISA were used to determine the serum SOD, MDA, T-AOC, and ox-LDL levels, respectively. RESULTS: Magnesium supplementation enhanced insulin sensitivity and decreased insulin resistance in diabetic rats mainly through increasing insulin receptor expression, affinity, and augmenting insulin receptor signaling. Magnesium supplementation also inhibited lipid peroxidation in diabetic rats and protected against pancreatic cell injury in diabetic rats. In addition, we found that β-arrestin-2 gene expression was suppressed in diabetes, which was possibly attributed to gene methylation modification, as β-arrestin 2 promotor was rich in methylation-regulating sites. Magnesium supplementation could affect β-arrestin-2 gene expression and methylation. CONCLUSION: Magnesium supplementation has a positive effect on insulin receptor activity and insulin sensitivity in type 2 diabetes.